Hydrogenation in multicrystalline silicon: The impact of dielectric film properties and firing conditions. (28th October 2019) - Sio, Hang Cheong; Phang, Sieu Pheng; Nguyen, Hieu T.; Hameiri, Ziv; Macdonald, Daniel
Abstract: Hydrogenation is a crucial step for improving the efficiency of multicrystalline silicon solar cells. In this work, we investigate the influence of different firing and annealing conditions on the efficacy of bulk hydrogenation in state‐of‐the‐art high‐performance multicrystalline silicon, for a range of hydrogen‐containing dielectric layers. All of the dielectric films studied, including aluminium oxide, amorphous silicon, and silicon nitride deposited with different tools, yield similar bulk lifetimes when annealed at optimal conditions. However, the optimal conditions vary between films, depending on the film properties. The overall hydrogenation effect does not appear to be affected by the cooling rate used during firing or by the application of illuminated annealing, performed at 250 ° C under 8 sun illumination. Moreover, we monitor in situ changes in the recombination behaviour of grain boundaries during the hydrogenation process, using a micro‐photoluminescence spectroscopy system with a temperature controlled stage. It is found that the hydrogenation reaction occurs at the annealing temperature range between 400 ° C and 500 ° C. Abstract : We investigate the influence of different firing and annealing conditions on the efficacy of bulk hydrogenation in state‐of‐the‐art high‐performance multicrystalline silicon, for a range of hydrogen‐containing dielectric layers. All of the dielectric films studied, including aluminium oxide, amorphous silicon, and silicon nitride deposited with different tools, yield similar bulk lifetimes when annealed at optimal conditions. In situ micro‐photoluminescence spectroscopy measurement on grain boundaries reveals that the hydrogenation reaction occurs between 400°C and 500°C.